2011
DOI: 10.1017/s0967199410000559
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal induction and semen characteristics of tambaqui Colossoma macropomum

Abstract: In the hatchery-bred tambaqui Colossoma macropomum, spontaneous semen release does not occur, and hand-stripping produces reduced semen volume. The goal of this work is to evaluate the effects of hormonal induction with carp pituitary extract (CPE) on both qualitative (visual aspect, pH, motility, viability and morphological abnormalities) and quantitative (volume, concentration and number of spermatozoa per ejaculate) traits of tambaqui semen. Eleven males were treated with CPE (induced), and 11 were left unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 11 publications
1
26
0
7
Order By: Relevance
“…These tests are implemented in the PROC GLM and PROC GENMOD procedures, respectively. MiraLópez et al (2010) for the same specie (89.0%) and for other species (Streit Jr et al 2008;Povh et al 2010;Maria et al 2011;Streit Jr et al 2012). In addition, no reference range of sperm motility was available for L. marmoratus in Brazil.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…These tests are implemented in the PROC GLM and PROC GENMOD procedures, respectively. MiraLópez et al (2010) for the same specie (89.0%) and for other species (Streit Jr et al 2008;Povh et al 2010;Maria et al 2011;Streit Jr et al 2012). In addition, no reference range of sperm motility was available for L. marmoratus in Brazil.…”
Section: Methodsmentioning
confidence: 91%
“…A significant difference was only in the frequency of loose heads, which was lower in the treatments with 0.4 and 0.6 Ovopel pellet/kg live weight (10.32 and 41.67%, respectively). A number of studies have shown high frequencies of secondary sperm defects in fish, particularly loose heads and tails (Streit Jr et al 2008;Maria et al 2011). These high frequencies of secondary abnormalities might be related to the procedure of smear preparation or semen collection, environmental temperature, diseases, animal feeding and sperm duct problems (Herman et al 1994).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 100 spermatozoids were observed on each slide, and the number of anomalous sperm was expressed as a percentage of the total number of cells evaluated. Based on Maria et al (2012), morphologically anomalous sperm were defined by the following characteristics: detached head, macrocephalic, microcephalic, degenerated head, proximal and distal cytoplasmic drops, degenerated mid-piece and bent, broken, coiled or short tail.…”
Section: Assessment Of Sperm Viability Morphology and Seminal Plasmamentioning
confidence: 99%
“…There are several studies on the reproduction of C. macropomum (Maria, Azevedo, Santos, & Carneiro, ; Martins et al, ; Varela Jr et al, ), some of which even examined sperm quality using ( casa ) in fresh sperm (Gallego et al, ; Maria et al, ; Melo‐Maciel, Nunes et al, ; Pires et al, ) and cryopreserved sperm (Gallego et al, ; Melo‐Maciel, Leite‐Castro et al, ). However, there are no reports on evaluation using casa software on the quality of cooled semen of C. macropomum .…”
Section: Introductionmentioning
confidence: 99%